Climate Policy and the Problem of Competitiveness: Border Tax Adjustments or Integrated Emission Trading? - Andreas Löschel; Victoria Alexeeva-Talebi; Tim Mennel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
In the absence of an international agreement on climate policy, unilateral carbon abatement creates two problems: It tends to have a detrimental effect on domestic competitiveness, and it leads to an increase in carbon emissions abroad (leakage). This paper analyses two policies that have recently been proposed to mitigate these problems: Border tax adjustments (BTA) and integrated emission trading (IET). The former policy levies a quantity-based, the latter an emission based duty on imports from non-abating countries. In a stylised two-country model we demonstrate that the policies address both problems. However, BTA protects domestic competitiveness more effectively, while IET achieves a greater reduction in foreign emissions. A computational general equilibrium analysis of the unilateral abatement policy adopted by the European Union confirms our theoretical insights for the sectors covered by the offsetting measures. However, the implications for the competitiveness of noncovered sectors are negative. These two effects constitute the central trade-off in the implementation of both policies.
Keywords: F18; Q48; D58; H23; 330; Border Tax Adjustments; Climate Policy; Competitiveness; Emission Trading; Klimaschutz; Internationaler Wettbewerb; Border Tax Adjustment; Zoll; Emissionshandel; Außenwirtschaft; Zwei-Länder-Modell; Allgemeines Gleichgewicht; Theorie; Welt; EU-Staaten